2020
DOI: 10.3389/fcell.2020.545852
|View full text |Cite
|
Sign up to set email alerts
|

Amnion-Derived Mesenchymal Stem Cell Exosomes-Mediated Autophagy Promotes the Survival of Trophoblasts Under Hypoxia Through mTOR Pathway by the Downregulation of EZH2

Abstract: Human amnion-derived mesenchymal stem cells (AD-MSCs) have been reported as a promising effective treatment to repair tissue. Trophoblast dysfunction during pregnancy is significantly involved in the pathogenesis of preeclampsia (PE). To understand how AD-MSCs regulated trophoblast function, we treated trophoblasts with AD-MSC-derived exosomes under hypoxic conditions. The treatment markedly enhanced the trophoblast proliferation and autophagy. Furthermore, significant decrease of EZH2 levels and inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…For a better understand the roles of 10 hub genes, there is a need to perform a more systematic analysis through pathway enrichment in DAVID database. In particular, we found that the mTOR, which is involved in the regulation of autophagy and inflammation signaling pathway ( Chu et al, 2020 ; Yao et al, 2020 ) was enriched. Further study found that mTOR signaling pathway is inhibited in CUMS rat model, which is in agreement with the results reported previously ( Zhang et al, 2020 ; Zhuo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For a better understand the roles of 10 hub genes, there is a need to perform a more systematic analysis through pathway enrichment in DAVID database. In particular, we found that the mTOR, which is involved in the regulation of autophagy and inflammation signaling pathway ( Chu et al, 2020 ; Yao et al, 2020 ) was enriched. Further study found that mTOR signaling pathway is inhibited in CUMS rat model, which is in agreement with the results reported previously ( Zhang et al, 2020 ; Zhuo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…SQSTM1 is involved in the regulation of autophagy and inflammation ( Chu et al, 2020 ; Yao et al, 2020 ). The serum level of TNFα was increased in MDD patients, which was associated with depressive symptoms ( Alvarez-Mon et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due in part to studying the paracrine effects of stem cell therapy, this speci c therapy has been mechanistically linked to the inherited functions of secreting exosomes [24]. Recently, research suggested HUCMSC-originated exosomes might be an innovative direction for therapeutic approaches against PE by accelerating trophoblast cell invasion and migration [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…EZH2 silencing promoted autophagy in endometrial cancer cells. Meanwhile, by activating the mTOR signaling, its overexpression reduced the autophagy and survival of trophoblasts in the trophoblastic disease ( Wang et al, 2018 ; Chu et al, 2020 ). Furthermore, EZH2 has been identified to be a promising tumor biomarker ( Cai et al, 2011 ), and it represents a prognostic biomarker associated with immunosuppression in esophageal squamous carcinoma and hepatocellular carcinoma ( Liu et al, 2016 ; Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%